Formulasi Kebijakan Bullying Untuk Pendidikan Jenjang Sekolah Dasar - Ajeng Anindya Murtini; Ghulam Maulana Ilman; Anggraeny Puspaningtyas (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2023)
Bullying (known in Indonesian as "repression/risak") is any form of oppression or violence carried out intentionally by one person or group of people who is stronger or more powerful towards another person, with the aim of hurting and is carried out continuously. Bullying often occurs among high school, middle school and even elementary school students. Like the bullying that happened at SDN 1 Biting. Therefore, a policy or regulation is needed to stop bullying. The author uses the policy formulation from Thomas R. Dye in researching bullying cases.